Perspectiva Histórica dos Cuidados de Enfermagem ao Doente Mental - Ferreira, Loide (2006)
The concept of caring in nursing has changed throughout the years. Nursing has developed to meet the needs of the population and to adapt at the same time to scientific knowledge, which has taken another dimension, and technical demand. Every field in nursing gains new formas as it evolves, namely the mental health and psychiatric fields. We start by describing the dominant beliefs of society in the past regarding mental health. We will then talk about mental patients in Portugal from the 16th Century on (1539-1850) and how they were cared for, underlining the first psychiatric institution - Rilhafoles Hospital. We will elaborate on the more common treatments in psychiatry, the purposes they served and how the nursing staff intervened in their application. Finally, we will put the evolution of nursing care to the mental patients into perspective, from the begining of the 20th century, as well as the development of nursing schools in the field of mental and psychiatric health.